PENGEMBANGAN BOOKLET CIRI DAN KLASIFIKASI MAKHLUK HIDUP SEBAGAI BAHAN AJAR IPA KELAS VII SMP NEGERI 4 RAMBAH - dahlia; Mubarrak Jismi; Rahayu Sefni; Brahmana Eti Meirina; Purnama Arief Anthonius (Jurnal Edu Research, 2026)
This research aims to determine the suitability of a booklet on the characteristics and classification of living things as science teaching material. This research was carried out at SMP Negeri 4 Rambah in April-September 2023. This type of research is research and development of the modified Borg and Gall model. The research population and sample were all 20 class VII students of SMP Negeri 4 Rambah, Rambah District. The research sampling technique used was total sampling. Data were collected using non-tests in the form of questionnaires and data were analyzed descriptively. The results of the research show that the development of a science booklet on the characteristics and classification of living things for students at SMP Negeri 4 Rambah as a whole is included in the "very feasible" category with an average percentage of 83.1%. Based on the validation of language experts with a percentage of 92.5%, it is included in the "very worthy" category, the validation of material experts with an average percentage of 69.2% is included in the " worthy" category, and the validation of media experts with a percentage of 87.5% is included in the “very worthy” category. Meanwhile, for individual trials the average percentage gain was 74.3%, including in the "worthy" category, for small group trials the average percentage of 85.83% was included in the " very worthy" category, and for field trials the average percentage gain was 84. 7% falls into the “very worthy” category.